The Impact Of The Covid-19 Crisis On Consumer Behavior Online Shopping In Wisma Atlet 2 Quarantine Area, Jakarta - Marchelina Febe; Selia Ilena (Psycho Idea, 2021)
This study aims to see whether there is an impact during the Covid 19 pandemic on online shopping behaviour, especially for volunteers and people who are in the quarantine area of Wisma Atlet 2. Where the independent variable of this study is crisis covid 19, which will affect the dependent variable, namely consumer behavior towards online shopping. This research was conducted because currently, Indonesia is experiencing the Corona Virus or more. They are known as Covid 19. Handling and prevention efforts continue to be carried out to fight COVID-19, one of which is by carrying out quarantine both independently and in bulk. One of the places in Jakarta that is used as a place for quarantine is Wisma Atlet 2. Therefore, researchers want to see whether this pandemic can affect someone in shopping online. This research is a quantitative study that uses a questionnaire from Icek Ajzen (Ajzen, 1991) as the main technique of data collection.The results show that online shopping behaviour has increased during the quarantine period.